Choreographed by situation : self-organizing choreography and the dancer’s agencement - Orpana, Mikko (Taideyliopiston Teatterikorkeakoulu, 2022)
There are many ways to approach self-organizing or improvised choreography. In this artistic research the choreography is approached as a self-organizing system and investigated for the requirements that this kind of approach demands from the choreographic thinking and practice and the dancer’s work to make the self-organization happen. This commentary will go through the following key concepts from art, scientific thinking and philosophy: choreography and choreographer ; composition, assemblage and agencement ; emergence ; systems theory ; situation ; embodied mind ; improvisation ; choreographic knowledge. This commentary also contains thorough analysis of three performances and one workshop that were done during the years 2011-2017.
My personal background in dance - early connections to dance and choreography and my years in the field -- 1. Introduction -- 2. The key concepts for the research -- 3. Artistic works for the research -- 4."United States of Mind" -- 5. "Dance & Philosophy" (workshop) - A philosophical inquiry for the dancer’s agency in my research -- 6. Conclusions -- 7. Bibliography.
Keywords: Dance.; Dancers.; Choreography.; Choreographers.; Creative ability.; Art--Philosophy.; System theory.; Mind and body.; Improvisation in art.; Art--Research.; Workshops.; Private&Common; tanssi; tanssijat; koreografit; koreografia; luovuus; taidefilosofia; systeemiteoria; mind and body; improvisointi; taiteellinen tutkimus; tanssiteokset; työpajat; fi=koreografia|sv=koreografi|en=Choreography|